GARLIC AMELIORATES HISTOLOGICAL CHANGES IN THE UTERINE EPITHELIUM OF LEAD INDUCED MICE: Garlic Ameliorates Effect in The Uterine Epithelium - Waseem, Naureen; Butt, Shadab Ahmed; Hamid, Shabnam (Pakistan Armed Forces Medical Journal, 2015)
Objective: To evaluate the protective role of garlic extract on the histoloy of the uterine epithelium exposed to lead acetate in an animal model. Study Design: Laboratory based randomized control trial. Place and Duration of Study: Department of Anatomy, Army Medical College in collaboration with National Institute of health from April to June 2013. Material and Methods: Thirty female BALBc mice were selected. Ten animals were placed in each group. Group A being the control was given normal diet. Group B was given lead acetate at a dose of 30 mg/kg/day. Group C was given lead acetate 30 mg/kg/day and garlic extract 500 mg/kg/day through oral gavage tube for 60 days. Animals were sacrificed and dissected at the end of 60 days. Right uterine horn was processed, embedded and stained for histological study. Height of epithelium was measured. It was taken from apical to basal end of the cells. Results: There was increase in height of the lining epithelium of uterus in group B, mean value 19.70 ± 4.81 µm when compared to Group A, with mean value 13.25 ± 2.37 µm. The height of the epithelium was relatively reduced in group C, with mean value 14.50 ± 2.30 µm when compared with group B. In group C results were same as Group A. The p values were 0.001 when group A was compared to group B, 0.688 when group A was compared to group C and 0.005 when group B was compared to group C. Conclusion: The height of epithelium was markedly increased in lead acetate treated group which returned to normal when co treated with garlic extract. Hence garlic ameliorated the changes induced by lead.